Cavonus Sharp, 1875 (Coleoptera: Scarabaeidae: Dynastinae: Pentodontini: Pseudoryctina) in Western Australia with description of a new species and the female of Cavonus sculpturatus Blackburn, 1888 - Hutchinson, Paul M.; Allsopp, Peter G. (Zootaxa, 2020)
The species of Cavonus Sharp, 1875 (Coleoptera: Scarabaeidae: Dynastinae: Pentodontini: Pseudoryctina) from Western Australia, Australia are revised and Cavonus fovealacus new species is described from southwestern Western Australia. The female attributed to Epironastes nigrisetosus Carne, 1957 is redescribed as the female of Cavonus sculpturatus Blackburn, 1888, as is the male of C. sculpturatus. Cavonus latecavatus Dupuis, 2017, from near Menzies in southwestern Western Australia, is transferred to Carneoryctes Özdikmen, 2009 as Carneoryctes latecavatus (Dupuis), new combination. Habitat descriptions, a distributional map, and revised keys to accommodate the new species are presented.